أدب الأطفال عند مصطفى عبد الفتاح: قراءات مختارة في بعض أعماله القصصية: Childrens’ Literature According to Mustafa Abdel Fattah: Selected Readings of Some of His Short Stories - Aljomaa, Alaa Alddin Ibrahim; Mohd Shahrizal Bin Nasir; Alawadi, Elsayed Mohamed Salem (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
يهدف هذا البحث إلى التعرّف على أدب الأطفال عند مصطفى عبد الفتاح من خلال الخوض في قراءات مختارة لبعض أعماله القصصيّة. كما يستعرض البحث جزءًا من السيرة الذاتية للكاتب، بالإضافة إلى تناول مفهوم أدب الأطفال بشكلٍ عام، والذي يحتوي على قيم تربي الأبناء وتعزز أخلاقهم. يتبع هذا البحث المنهج الوصفي التحليلي، وذلك من خلال جمع المعلومات والدراسات المتعلقة بأدب الأطفال بشكلٍ عامِ، ومصطفى عبد الفتاح بشكل خاص من مصادر مختلفة وإجراء قراءة متأنية لعينةٍ مختارة من القصص الموجهة للأطفال التي كتبها مصطفى عبد الفتاح. إن استخلاص أبرز خصائصه الفنية وملامح أسلوب مصطفى عبد الفتاح في كتابة قصص الأطفال وصولاً إلى استخلاص الاستنتاجات. يتناول هذا البحث أدب الأطفال في الأعمال الإبداعية للكاتب مصطفى عبد الفتاح في القصص القصيرة الموجهة للأطفال من خلال التركيز على قراءة وتحليل ثلاث قصصٍ قصيرةٍ من أعمال الكاتب: «الأمل»، و«الصديقان»، و«الطاووس الجائع». وقد أظهرت النتائج أن الكاتب برع في عرض الأحداث بشكل منطقي ومتسلسل. تحتوي قصص الكاتب القصيرة على العديد من القيم والمفاهيم التربوية، كما استخدم الكاتب لغةً بسيطةً وسلسةً تتناسب مع المرحلة العمرية التي كان يخاطبها. ولهذا البحث عدة مضامين بحثية، منها فتح آفاق جديدة أمام الباحثين لإجراء المزيد من الدراسات المتعمقة والشاملة حول أعمال هذا الكاتب الرائد في مجال أدب الأطفال. وبالإضافة إلى ذلك، دفع الباحثين وطلاب الدراسات العليا من النقاد والباحثين الأدبيين إلى استكشاف جوانب أخرى من إبداع مصطفى عبد الفتاح وإجراء دراسات تحليلية ونقدية لأعماله الأدبية. ABSTRACT This research aims to learn about childrens’ literature by Mustafa Abdel Fattah through some of his short stories. The research also reviews part of the writer’s biography, in addition to addressing the concept of childrens’ literature according to his point of view, which contains values that raise children’s development and enhance their morals. This research follows the descriptive analysis method, by collecting information and studies related to childrens’ literature in general and Mustafa Abdel Fattah’s views in particular from various sources and conducting an analysis of several selected sample of his short stories. Extracting its most prominent artistic characteristics and features of Mustafa Abdel Fattah’s style in writing short stories for children, leading to drawing conclusions of this research. Besides, this research deals with childrens’ literature related to the creative works of Mustafa Abdel Fattah in short stories for children through focusing on reading and analyzing three short stories from the writer’s works which are “Hope”, “The Two Friends” and “The Hungry Peacock”. The findings show that the writer excelled in presenting his short stories in a logical and sequential manner for children. The writer’s short stories contain many educational values and concepts, and the writer also used simple and appropriate language to the children. This research could have several research implications, including opening new horizons for researchers to conduct more in-depth and comprehensive studies on the works of this pioneering writer in the field of childrens’ literature. In addition, it prompted researchers and graduate students, including critics and literary researchers, to explore other aspects of Mustafa Abdel Fattah’s creativity and to conduct analytical and critical studies on his literary works.